Productive zakat: a robust model for the economic welfare of mustahiq - Kakar, Ajmal; Akbar, Mohamed Aslam (Academic Inspired Network, 2025)
The principal aim of this article is to scrutinise the efficacy of productive zakat within the context of zakat institutions in supporting startups and entrepreneur mustahiq. A mixed-methods approach combining qualitative and quantitative data, relying on library research, was employed to achieve the study’s main objectives. The significant findings reveal that not only is there no profound rejection of zakat disbursement in the form of investment from the period of the Prophet (saw) and jurisprudence, but also there exists motivation and a clear guideline for contemporary scholars to expand the concept of zakat investment based on the current needs of Muslim societies. Furthermore, some success stories of zakat institutions from the literature revealed that zakat management has been transformed to enable more effective collection and distribution, thereby decreasing poverty and encouraging the poor to be involved in the production process and to gain income for themselves. In the meantime, several challenges identified in the existing literature indicate the need for further improvement. Notably, one of the main challenges lies in the limited consideration and practical application of productive Zakat within international contexts. Subsequently, the study offers valuable recommendations for enhancing zakat institutions' policies on productive zakat distribution. It serves as a foundation for future research, illuminating avenues for further exploration of this subject.